Kapasitas ultimate balok tersusun kayu - plywood terhadap kekuatan lentur balok - Edi Purwanto (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
The use of wood in construction is very much utilization. Wood is known as plywood or plywood isone of the commonly used wood products. Use plywood nowadays more as a raw material in fur-niture. Plywood timber has not been widely used as a construction material that can withstandstructural loads such as beams. This study was conducted to determine the magnitude of the in-crease load capacity that can be supported by wood-plywood which has been prepared with a par-ticular arrangement, especially in bending strength, and the possibility to be applied as a struc-tural beam for a relatively heavy load. By knowing the flexural strength of the beam composed ofwood - plywood is expected to optimize the use of wood in construction plywood as a material thatis able to receive the load on the structure.